An electroencephalographic study in birth asphyxia and correlation of electroencephalographic pattern with neurodevelopment outcome at 6-month age - Jain, Ashish; Shrivastav, Jyotsna; Prajapati, Jyoti (Indian Journal of Child Health, 2018)
Background: Perinatal asphyxia is one of the most common medical emergencies of newborn and important cause of neonatal morbidity and mortality. In India, about 1 million babies suffer from birth asphyxia every year, and it is responsible for nearly 28.8% of the neonatal deaths and the subsequent major sequelae. Objectives: The objective of the study was to evaluate the clinico-etiological and electrophysiological profile of neonates with birth asphyxia and its correlation with the neurodevelopment outcome at 6 months of age. Methods: In this prospective observational follow-up study, 50 neonates of >35 weeks of gestation with a history of birth asphyxia were included. Electroencephalographic (EEG) was performed within the first 72 h of life or as soon as neonate was stable. Follow-up visits were scheduled as per NNF guidelines at 6, 10, and 14 weeks, 3 and 6 months of age. Detailed neurological examination, neurodevelopment and tone were assessed by Denver II and Amiel–Tison method, respectively, on every visit. Results: All neonates were on hypoxic-ischemic encephalopathy (HIE) Stage I had normal EEG recording; 36.7% with HIE Stage II had abnormal EEG recording while 100% the neonates of HIE Stage III showed abnormal EEG. All neonates, who had normal EEG recording, survived, and 96.5% (n=28) of them show normal neurodevelopment outcome. 3.7% (n=1) showed developmental delay. All the neonates who had abnormal background on EEG showed adverse outcome. 50% of them expired and rest 50% had abnormal neurodevelopment outcome on follow-up. Conclusion: The severity of encephalopathy in asphyxiated neonates correlates well with the abnormalities on EEG records.